Improvement of ecosystem quality in National Key Ecological Function Zones in China during 2000–2015. (15th December 2022) - Zhang, Mengyu; Zhang, Li; He, Honglin; Ren, Xiaoli; Lv, Yan; Niu, Zhong'en; Chang, Qingqing; Xu, Qian; Liu, Weihua
Abstract: Improving ecosystem quality is the ultimate goal of ecological restoration projects and sustainable ecosystem management. However, previous results of ecosystem quality lack comparability among different regions when assessing the effectiveness of ecological restoration projects on the regional or national scales, due to the influence of geographical and climatic background conditions. Here we proposed a new index, ecosystem quality ratio (EQR), by integrating the status of landscape structure, ecosystem services, ecosystem stability, and human disturbance relative to their reference conditions, and assessed the EQR changes in China's counties and National Key Ecological Function Zones (NKEFZs) from 1990 to 2015. The results showed that the average ecosystem quality of China's counties deviated from the reference condition by 28%. EQR decreased by 1.2% during 1990–2000 but increased by 3.7% during 2000–2015. Those counties with increasing EQR in 2000–2015 occupy 64.7%, with obviously increasing counties mainly located in the water conservation, biodiversity maintenance, and water and soil conservation types of NKEFZs. The EQR increase in counties within NKEFZs was 3.65 times that outside of NKEFZs. Remarkable improvement of ecosystem quality occurred in the forest region in Changbai Mountain, biodiversity and soil conservation region in Wuling Mountains, and hilly and gully region of Loess Plateau, where EQR increases mainly resulted from the conversion of farmland to forest or grassland and consequent increases in ecosystem services and stability. The magnitude of EQR enhancement showed a positive relationship with the increase in forest and grassland coverage in NKEFZs. Our results highlight the important role of ecological restoration projects in improving ecosystem quality in China, and demonstrate the feasibility of the new index (EQR) for the assessment of ecosystem quality in terms of ecosystem management and restoration. Highlights: An ecosystem quality index relative to reference conditions was proposed. Ecosystem quality of China's counties deviated from the reference condition by 28%. Remarkable improvement in ecosystem quality in China's counties after 2000. The increase due to changes in its components induced by ecological projects. Magnitude of its enhancement was positively correlated with forest/grass increase.